ITGB6 may promote proliferation and invasion in pancreatic cancer - Chao Zhong; Zhi-Xi Li; Ling-Jing Yang; Gang Wu; Bo Xiang; Yu-Lan Wang; Qing Zhou (Archives of Medical Science, 2021)
Introduction The ITGB6 gene encoding a protein that can regulate the integrin v6 heterodimer protein expression in different status was shown to play an important role in multiple human cancers, such as brain cancer, colon cancer and oral cancer, and is related to clinical progression. This study aims to explore the function and the mechanism of the ITGB6 gene or protein in pancreatic cancer.